The Human Osteological Collection of Vilnius University - Kozakaitė, Justina; Brindzaitė, Rūta; Miliauskienė, Žydrūnė; Žalnora, Aistis; Jankauskas, Rimantas (Archaeologia Lituana, 2020)
This article briefly presents the history of the human osteological collection stored at the Faculty of Medicine of Vilnius University. The birth of such collection can be traced back to the mid-19th century (1855) with the establishment of the Museum of Antiquities. Until the mid-20th century, human skeletal remains were gathered sporadically and selectively, by collecting either skulls or long bones. Since the late 20th century, the policy of selection has changed and nowadays the collection consists of systematically assembled anthropological material of scientific value. The assemblage currently comprises more than 9.000 skeletal remains dating back from the Mesolithic to the Late Modern Era.
Keywords: osteological collection; research collection; anthropology; Vilnius University; Lithuania